85.1k views
2 votes
#1: Solve the linear system below using the elimination method. Type your

answer as an ordered pair in the form (#,#).*
2x + 5y = -16
-3x + 7y = -5

User Simon Lee
by
5.6k points

1 Answer

5 votes

Answer:


(-3,-2)

Explanation:

First, you need to get one like term in each equation the same in order to eliminate. To do less damage to the equation, we'll use the x terms.

To get the x terms the same, multiply both equations by the opposite x term:


-3(2x+5y)=-3(-16)\\\\2(-3x+7y)=2(-5)

Simplify by multiplying. Use the distributive property for the left side (remember, two negatives make a positive and a negative multiplied by a positive will always be negative):


-3(2x)-3(5y)=-3(-16)\\\\2(-3x)+2(7y)=2(-15)\\\\\\-6x-15y=48\\\\-6x+14y=-10

Now subtract all like terms. The x terms cancel out:


-6x-(-6x)=0\\\\-15y-14y=-29y\\\\48-(-10)=58\\\\-29y=58

Now solve the new equation for y. Isolate the variable by using inverse operations. The term can be seen as -29×y. In order to isolate the variable, use division (opposite of multiplication). Divide both sides by 29:


(-29y)/(29) =(58)/(29) \\\\-1y=2

Make the variable positive. Multiply both sides by -1:


-1(-1y)=-1(2)\\\\y=-2

The value of y is -2. Insert this value into either original equation:


2x+5(-2)=-16

Solve for x. Simplify multiplication:


2x-10=-16

Use inverse operations to get like terms on the same side of the equation. Add 10 to both sides (addition is the opposite of subtraction) to cancel out the -10 on the left:


2x-10+10=-16+10\\\\2x=-6

Isolate the variable using inverse operations. The x term can be seen as 2×x. Division is the opposite of multiplication, so divide both sides by 2:


(2x)/(2)=(-6)/(2) \\\\x=-3

The value of x is -3. Therefore, the solution to the system is:


(-3_(x),-2_(y))

:Done

User Liolik
by
5.6k points